Optimal taxation with endogenous return on capital - Kristjánsson; Arnaldur Sölvi (University of Iceland, Institute of Economic Studies (IoES), 2024)
This paper characterises optimal taxation when rates of return are affected by effort, ability, and financial advice. When the government observes wealth and capital income, the optimal marginal tax rate on capital income is positive, whereas the rate on wealth is negative in the baseline model. When wealth is not observed, the optimal marginal tax rate on capital income remains positive. If inequality in labour market productivity is sufficiently large compared to investment ability, the marginal tax rate on labour income exceeds the rate on capital income, and vice versa.
Keywords: G11; H21; H24; 330; Optimal taxation; capital taxation; endogenous return on capital